Toune Mosquee in Kaffrine, Senegal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Jathropha plants are of great economic value in Toune Mosquee village, in Kaffrine, Senegal. Kaffrine is one of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) benchmark research sites. Read more about the work done in Kaffrine, Senegal.